Participating together: dialogic space for children and architects in the design process. Issue 2 (4th March 2017) - Birch, Joanna; Parnell, Rosie; Patsarika, Maria; Šorn, Maša
ABSTRACT: Typically enmeshed in the 'voice' perspective within children's participation debates, there are currently sporadic insights into designer–child creative dialogue. Drawing on the findings of a Leverhulme Trust-funded research project, this paper articulates moments of dialogue between architects and children in spatial design processes, whose spatial and symbolic qualities help to understand the interactions and meeting of cultures. Several authors have discussed the transformational potential for adults and children to 'co-author' identities in dialogical contexts. The paper builds on this body of research to suggest that design dialogue offers the space, literally and metaphorically, for children and architects to participate together. Identifying the qualities of the dialogic design space as potentially present in children's and adults' everyday cultures and interdependent relations, it is proposed that this dialogical framework might diversify architects' and children's roles in the design process and enrich practices and perceptions of design participation.